A study of the characteristics of a mango jelly candy formulated with gelatin and honey - Ramdani, Sigit; Saputrayadi, Adi; Marianah, Marianah; Nazaruddin, Nazaruddin (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
Jelly confectionery is a soft textured confectionery processed with the addition of hydrocolloid components such as agar, gum pectin, starch, carrageenan, gelatin and others, which are used to modify the texture in order to obtain a chewy product and need to be moulded. The aim of this study was to determine the effect of the formulation of the addition of gelatin and honey on the chemical and organoleptic properties of mango jelly candy and to determine the correct formulation of gelatin and honey in the manufacture of mango jelly candy based on the panelists' preference. The method used in this research is an experimental method using a completely randomised design (CRD) with two factors, namely the formulation of gelatin and honey in the production of jelly candy, consisting of 5 treatments: P1 = 10% gelatin + 20% honey, P2 = 9% gelatin + 25% honey, P3 = 8% gelatin + 30% honey, P4 = 7% gelatin + 35% honey, P5 = 6% gelatin + 40% honey. The research data were analysed using ANOVA analysis of variance at the 5% real level and further tests were carried out using the BNJ test at the 5% level. Based on the statistical results, it is known that the formulation of gelatine and honey has a significant effect on the vitamin C and reducing sugar levels and on the organoleptic properties of all parameters, but does not have a significant effect on the moisture content and ash content of the mango jelly candies tested. In conclusion, the best treatment was P5 (6% gelatin + 40% honey) with respect to water content, ash, vitamin C and reducing sugars.